Nonlinear predictive control theory and practice - Kouvaritakis, Basil; Cannon, Mark 1971- (Institution of Engineering and Technology, 2001)
The book is divided into 4 parts and comprises 12 chapters dealing with the following subjects: nonlinear model predictive control applications; output feedback and tracking of nonlinear systems; model predictive control of nonlinear parameter varying systems via receding horizon control Lyapunov functions; nonlinear model-algorithmic control for multivariable nonminimum-phase processes; open-loop and closed-loop optimality in interpolation MPC; closed-loop predictions in model based predictive control of linear and nonlinear systems; computationally efficient nonlinear predictive control algorithm for control of constrained nonlinear systems; long-prediction-horizon nonlinear model predictive control; nonlinear control of industrial processes; nonlinear model based predictive control using multiple local models; and neural network control of a gasoline engine with rapid sampling.